Controversies in faith and health care. Issue 10005 (31st October 2015) - Tomkins, Andrew; Duff, Jean; Fitzgibbon, Atallah; Karam, Azza; Mills, Edward J; Munnings, Keith; Smith, Sally; Seshadri, Shreelata Rao; Steinberg, Avraham; Vitillo, Robert; Yugi, Philemon
Summary: Differences in religious faith-based viewpoints (controversies) on the sanctity of human life, acceptable behaviour, health-care technologies and health-care services contribute to the widespread variations in health care worldwide. Faith-linked controversies include family planning, child protection (especially child marriage, female genital mutilation, and immunisation), stigma and harm reduction, violence against women, sexual and reproductive health and HIV, gender, end-of-life issues, and faith activities including prayer. Buddhism, Christianity, Hinduism, Islam, Judaism, and traditional beliefs have similarities and differences in their viewpoints. Improved understanding by health-care providers of the heterogeneity of viewpoints, both within and between faiths, and their effect on health care is important for clinical medicine, public-health programmes, and health-care policy. Increased appreciation in faith leaders of the effect of their teachings on health care is also crucial. This Series paper outlines some faith-related controversies, describes how they influence health-care provision and uptake, and identifies opportunities for research and increased interaction between faith leaders and health-care providers to improve health care.